(3ecHK eJHhYH(B: (3GdYGUaI (B:s (3eSQMjGJ (B/s - (3TcSHjQ, hdjes; (3CHh GdYHO OhOhs ((3GdLRGFQ (B:s (3GdeDSSI GdhWfjI ddafhf GdeWHYjI ,s, 1994)
(3jbOe dfG TjcSHjQ TNUjGJ NGdOI dGfYOe GHOG GdYKhQ YdjgG aj cd ReGf h ecGf afLOg jQGab HUaJg TGYQG GdQZHGJ GdLGeMI HUaI dG JNdh ef GYLGH h GaJJGf h cGfg jTYQ HGdYWa YdjgG ceG dh GfgG bO GJNPJ TcdG MjG ajQYi fTGJgG h jdGRegG MJi JfaLQ cGdYGUaI Hcd eG ajgG ef HQhb h QYhOs
Keywords: (3hdjGe TjcSHjQs; (3TNUjGJs